Vision of the II World Conference on Higher Education (WCHE, 2009) - doi: 10.4025/actascieduc.v32i1.9490 - Francisco Lopez Segrera (Universidade Estadual de Maringá, 2010)
The aim of this article is to offer some reflections on The Second World Conference on Higher Education (UNESCO, 2009), whose central topic was: "The new dynamics of Higher Education and Research for the Social Change and the Development". The Conference expressed its concern for the World recession and its negative impact on higher education. Forecasts and recommendations were formulated in order that the above mentioned recession does not affect the development of higher education and research. The main debate in the Conference was about a key alternative: higher education as "a public good", or as "a public service". In the Final Communiqué the first criterion prevailed.